The Fourth term of an A.P. is ten times the first. Prove that the sixth term is four times the second term.

Asked by sarika vijay kumar | 6th Sep, 2011, 05:34: PM

Expert Answer:

The formula for nth term of an A.p is a+(n-1)d,where a is the first term,d is the common difference.
Given,4th term=10 a.
now,sixth term=a+(6-1)d
Thus,sixth term=4(4a)=4(2nd term)

Answered by  | 6th Sep, 2011, 06:32: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.